Conceptual Model on the Influence of Environmental Awareness on the Effectiveness of Environmental Management System: Case Study of Oman Oil and Gas Operators - Said M., Al-Saqri; Sagaran, Gopal; Hock, Oo Yu; Ali Malik, Al Harthy; Asif, Mahbub Karim (2018)
This paper is intended to define the environmental awareness as a mediating variable that needs to be studied to ensure the effective implementation of the Environmental Management System. The model will look into the importance of environmental awareness at different level of an organization on improving the Environmental Management System and what are the identified factors to ensure it sustainability. Five (5) oil and gas operators in Oman will be chosen to examine the model. The organizations were selected based on different criteria; scope of activities, ISO 14001 certification and implementation and how large is the organization in terms of number of drilling units. The study will look into existing theoretical models examining the literature and address any areas to be improved. The outcome of this paper is a conceptual model that suggests how the existing Environmental Management System elements can be further improved by ensuring a comprehensive environmental awareness programs are implemented into those organizations.